Precise Genome Modification via Sequence-Specific Nucleases-Mediated Gene Targeting for Crop Improvement - Sun, Yongwei; Li, Jingying; Xia, Lanqin (Frontiers in Plant Science, 2016)
Genome editing technologies enable precise modifications of DNA sequences in vivo and offer a great promise for harnessing plant genes in crop improvement. The precise manipulation of plant genomes relies on the induction of DNA double-strand breaks (DSBs) by sequence-specific nucleases (SSNs) to initiate DNA repair reactions that are based on either non-homologous end joining (NHEJ) or homology-directed repair (HDR). While complete knock-outs and loss-of-function mutations generated by NHEJ are very valuable in defining gene functions, their applications in crop improvement are somewhat limited because many agriculturally important traits are conferred by random point mutations or indels at specific loci in either the genes’ encoding or promoter regions. Therefore, genome modification through SSNs-mediated HDR for gene targeting (GT) that enables either gene replacement or knock-in will provide an unprecedented ability to facilitate plant breeding by allowing introduction of precise point mutations and new gene functions, or integration of foreign genes at specific and desired ‘safe’ harbor in a predefined manner. The emergence of three programmable SSNs such as zinc finger nucleases (ZFNs), transcriptional activator-like effector nucleases (TALENs), and the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) systems has revolutionized genome modification in plants in a more controlled manner. However, while targeted mutagenesis is becoming routine in plants, the potential of GT technology has not been well realized for traits improvement in crops, mainly due to the fact that NHEJ predominates DNA repair process in somatic cells and competes with the HDR pathway, and thus HDR-mediated GT is a relative rare event in plants. Here, we review recent research findings mainly focusing on development and applications of precise GT in plants using three SSNs systems described above, and the potential mechanisms underlying HDR events in plant cells. We then address the challenges and propose future perspectives in order to facilitate the implementation of precise genome modification through SSNs-mediated GT for crop improvement in a global context.